Genetic parameters and trends of growth traits in community-based breeding programs of Abera sheep in Ethiopia - Alemayehu, Amelmal; Mirkena, Tadele; Melesse, Aberra; Getachew, Tesfaye; Haile, Aynalem (Taylor and Francis Group, 2023)
The objectives of the current study were to estimate the genetic parameters and genetic trends for growth traits, and to assess inbreeding levels of Abera sheep under community-based breeding programs (CBBPs) in Ethiopia. General linear model consisting of the fixed effects of sex, breeder cooperative, season and birth type was used to analyze growth traits. Variance components and genetic parameters were estimated within each breeder cooperative following univariate animal model based on the restricted maximum likelihood method. All fixed effects influenced (P < 0.05) the growth traits. Multivariate analysis was also employed to compute correlation estimates among growth traits. Based on the best fitted models, the direct heritability for weaning weight (WWT) and six-month weight (SMWT) in the six breeder cooperatives were in the ranges of 0.12 ± 0.12–0.38 ± 0.17 and 0.20 ± 0.10–0.49 ± 0.01, respectively. Range of positive genetic progress in WWT (0.15–0.44 kg) and SMWT (0.21–0.57 kg) was achieved in Abera sheep breeder cooperatives during selection years.